Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.7759/cureus.11035
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki Disease-Like Features in 10 Pediatric COVID-19 Cases: A Retrospective Study

Abstract: Children with coronavirus disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2), usually present with symptoms of mild upper respiratory tract infection without developing any significant complications. However, this observation has been rendered incautious by hundreds of clinical cases from around the world that have depicted a less benign multisystem inflammatory illness mimicking Kawasaki disease in COVID-positive pediatric patients. Our study aimed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…An observational study from the Bergamo province in Italy, which had a high rate of SARS-CoV-2 infections at that time, reported a 30-fold increased monthly incidence of KD in a cohort of children from February 18, 2020, to April 20, 2020, compared with a cohort of patients from the previous five years [ 14 ]. The same hyperinflammatory shock in children has also been observed in France, Spain, Portugal, and Pakistan [ 10 , 15 ]. Interestingly, some series noted frequent gastrointestinal symptoms, including bloodless diarrhea, abdominal pain, severe vomiting, and imaging revealed ascites and ileitis [ 7 , 14 ].…”
Section: Discussionsupporting
confidence: 55%
“…An observational study from the Bergamo province in Italy, which had a high rate of SARS-CoV-2 infections at that time, reported a 30-fold increased monthly incidence of KD in a cohort of children from February 18, 2020, to April 20, 2020, compared with a cohort of patients from the previous five years [ 14 ]. The same hyperinflammatory shock in children has also been observed in France, Spain, Portugal, and Pakistan [ 10 , 15 ]. Interestingly, some series noted frequent gastrointestinal symptoms, including bloodless diarrhea, abdominal pain, severe vomiting, and imaging revealed ascites and ileitis [ 7 , 14 ].…”
Section: Discussionsupporting
confidence: 55%
“…There has been a striking paucity of MIS-C cases from East Asia, despite the high incidence of KD in this geographic area ( Kim et al, 2020b ; Li et al, 2019 ). Only two cases of MIS-C have been reported to date in South Korea, and no cases have been reported in Japan or China ( Toyo Keizai Online COVID-19 Task Team, 2021 ), contrasting with the higher numbers of cases from the Americas, Europe, Africa, South Asia, and the Middle East ( Almoosa et al, 2020 ; Dufort et al, 2020 ; Falah et al, 2020 ; Feldstein et al, 2020 ; Jain et al, 2020 ; Kim et al, 2020a ; Kim et al, 2020b ; Lee et al, 2021 ; Mamishi et al, 2020 ; Ulloa-Gutierrez et al, 2020 ; Verdoni et al, 2020 ; Webb et al, 2020 ). Whether this is merely due to a lower number of COVID-19 cases in East Asia remains to be seen, bearing in mind the possibility of ascertainment bias ( Fig.…”
Section: Epidemiology Of Mis-c and Kdmentioning
confidence: 99%
“…One study only reported recurrent aphthous stomatitis in COVID-19 patients, and one study reported oral changes but failed to describe the type of changes noted. 10 , 11 …”
Section: Resultsmentioning
confidence: 99%